Different Angiogenic Potential in Low and High Grade Sporadic Clear Cell Renal Cell Carcinoma Is Not Related to Alterations in the von Hippel–Lindau Gene - Marcella M. Baldewijns; Iris J. H. van Vlodrop; Kim M. Smits; Peter B. Vermeulen; Gert G. Van den Eynden; Fiona Schot; Tania Roskams; Hein van Poppel; Manon van Engeland; Adriaan P. de Bruïne (Cellular Oncology)
Background: von Hippel–Lindau (VHL) inactivation is common in sporadic clear cell renal cell carcinomas (ccRCC). pVHL is part of the ubiquitin ligase complex that targets the alpha subunits of hypoxia-inducible transcription factor (HIF) for degradation under well-oxygenated conditions. In the absence of wild-type pVHL, as observed in VHL patients and most sporadic ccRCCs, constitutive upregulation of HIF results in transcriptional activation of angiogenesis-related genes, such as VEGF. Differences in angiogenic activity within the group of ccRCCs were reported and strong genotype-phenotype correlations were found in patients with VHL disease, raising a question about the importance of VHL inactivation status in angiogenic behaviour and tumour progression.